Occurrence of polybrominated diphenylethers, hexabromocyclododecanes, bromophenols and tetrabromobisphenols A and S in Irish foods. (April 2018) - Garcia Lopez, Monica; Driffield, Malcolm; Fernandes, Alwyn R.; Smith, Frankie; Tarbin, Jonathan; Lloyd, Antony S.; Christy, Julie; Holland, Melanie; Steel, Zoe; Tlustos, Christina
Abstract: The occurrence of polybrominated diphenyl ethers (PBDEs), hexabromocyclododecanes (HBCDs), tetrabromobisphenol A (TBBPA) and other phenolic brominated flame retardants (BFRs) in Irish foodstuffs has been assessed. A total of 53 food samples including eggs, milk, fish, fat and offal were tested. Eighty-one percent of the samples contained at least one measurable PBDE congener. The most abundant and frequently occurring congeners were BDE-47, BDE-49, BDE-99, BDE-100 and BDE-209 with the highest concentrations found in fish, fat and eggs. Summed concentrations for the measured PBDEs ranged from 0.02 μg/kg to 1.37 μg/kg whole weight. At least one HBCD stereoisomer was found in twenty-six percent of the samples with α-HBCD being the most frequently detected. The highest concentrations were found in fat and oily fish samples. TBBPA was only detected in one farmed salmon sample at 0.01 μg/kg. Bromophenol residues were found in fourteen out of the 53 samples, specifically in eggs and fish, with concentrations ranging from 0.28 to 0.98 μg/kg whole weight. These data contribute to the EU-wide EFSA risk assessment on these contaminants that is currently underway. Highlights: Occurrence data on PBDEs, HBCDs and TBBPA in Irish foodstuffs. Screening of phenolic BFRs. Occurrence of a wider range of BFRs in food.